Standardized Astragalus Mongholicus Bunge-Curcuma Aromatica Salisb. Extract Efficiently Suppresses Colon Cancer Progression Through Gut Microbiota Modification in CT26-Bearing Mice - Gu, Junfei; Sun, Ruolan; Wang, Qiaohan; Liu, Fuyan; Tang, Decai; Chang, Xiangwei (Frontiers in Pharmacology, 2021)
Altered gut microbiota and a damaged colon mucosal barrier have been implicated in the development of colon cancer. Astragalus mongholicus Bunge-Curcuma aromatica Salisb. (ACE) is a common herbal drug pair that widely used clinically to treat cancer. However, whether the anti-cancer effect of ACE is related to gut microbiota remains unclear yet. We standardized ACE and investigated the effects of ACE on tumour suppression and analyze the related mechanisms on gut microbiota in CT26 colon cancer-bearing mice in the present study. Firstly, 4 Flavonoids (calycosin-7-glucoside, ononin, calycosin, formononetin) and 3 astragalosides (astragaloside A, astragaloside II, astragaloside I) riched in Astragalus mongholicus Bunge, 3 curcumins (bisdemethoxycurcumin, demethoxycurcumin, curcumin) and 4 essential oils (curdione, curzerene, germacrone and β-elemene) from Curcuma aromatica Salisb., in concentrations from 0.08 to 2.07 mg/g, were examined in ACE. Then the results in vivo studies indicated that ACE inhibited solid tumours, liver and spleen metastases of colon cancer while simultaneously reducing pathological tissue damage. Additionally, ACE regulated gut microbiota dysbiosis and the short chain fatty acid content in the gut, repaired intestinal barrier damage. ACE treatment suppressed the overgrowth of conditional pathogenic gut bacteria, including Escherichia-Shigella, Streptococcus and Enterococcus, while the probiotic gut microbiota like Lactobacillus, Roseburia, Prevotellaceae_UCG-001 and Mucispirillum were increased. More interestingly, the content level of SCFAs such as propionic acid and butyric acid was increased after ACE administration, which further mediates intestinal SDF-1/CXCR4 signalling pathway to repair the integrity of the intestinal barrier, decrease Cyclin D1 and C-myc expressions, eventually suppress the tumor the growth and metastasis of colon cancer. To sum up, the present study demonstrated that ACE could efficiently suppress colon cancer progression through gut microbiota modification, which may provide a new explanation of the mechanism of ACE against colon cancer.